2012
DOI: 10.1371/journal.pgen.1002700
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition Order of Ras and p53 Gene Alterations Defines Distinct Adrenocortical Tumor Phenotypes

Abstract: Sporadic adrenocortical carcinomas (ACC) are rare endocrine neoplasms with a dismal prognosis. By contrast, benign tumors of the adrenal cortex are common in the general population. Whether benign tumors represent a separate entity or are in fact part of a process of tumor progression ultimately leading to an ACC is still an unresolved issue. To this end, we have developed a mouse model of tumor progression by successively transducing genes altered in adrenocortical tumors into normal adrenocortical cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
1
15
0
1
Order By: Relevance
“…Other ways to improve the outcome might be controlling different gene alterations in chronological order rather than simultaneously, for example, deleting Vhl first and then other genes after an interval. This suggestion is based on an observation that the tumor phenotype is directly shaped by the order of acquisition of genetic alterations 84 and that the order of genetic mutations influences the clonal evolution of cancer 85 . Altering genes in order rather than simultaneously might better resemble the natural process of tumorigenesis, although this manipulation would increase the difficulty of experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Other ways to improve the outcome might be controlling different gene alterations in chronological order rather than simultaneously, for example, deleting Vhl first and then other genes after an interval. This suggestion is based on an observation that the tumor phenotype is directly shaped by the order of acquisition of genetic alterations 84 and that the order of genetic mutations influences the clonal evolution of cancer 85 . Altering genes in order rather than simultaneously might better resemble the natural process of tumorigenesis, although this manipulation would increase the difficulty of experiments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the double mutation in the order of TP53 and NOTCH, which are representative tumorsuppressor and oncogenes, respectively, was frequently observed in early stage of esophageal carcinoma patients [53], whereas the reverse-ordered mutation is likely to lead to a metastasis progression in mouse experiments [63,64]. It was also shown that alteration of RAS, which is another oncogene, before loss of P53 formed a malignant tumor with metastatic behavior, but the reverseordered mutation resulted in benign tumors [2,65].…”
Section: Analysis Of Tumor Suppressor and Oncogenes With Respect To Omentioning
confidence: 99%
“…The first suggestion that the temporal sequence of two mutations might impact tumorigensis was in a mouse model of adrenocortical tumors[38]. When oncogenic Ras was over-expressed before loss of p53, highly malignant tumors with metastatic properties were formed in contrast to the benign tumors that resulted from the reverse mutational order.…”
Section: Mutation Order Mattersmentioning
confidence: 99%